(untitled) - Hibino, Tsuneji (Rutland, Vermont, 1968)
This book's audience is sure to be wide and varied as it is highly suitable as a school textbook, excellent background for the businessman or tourist, and interesting reading for all those who wish concise but ac-curate knowledge of the foremost country in Asia.
Keywords: Japan,Japan; Description and travel.,Socioeconomic conditions